Rozwój prywatnych ubezpieczeń zdrowotnych w Polsce - możliwości i bariery - Worach-Kardas, Halina; Słowińska, Justyna (The Development of commercial health insurance sector in Poland - the possibilities and limits, 2006)
The purpose of this article is to define the current state of voluntary health insurance sector in Poland as well as their place in the health care system. The paper presents an analysis of having the individual health insurance products in Polish households also. The main possibilities and limits of the further growth of commercial health insurance market are presented in the paper as well.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1133, s. 584-591